Argumentationsanalyse. Grundtræk af en modulær sprogvidenskabelig tilgang - Nølke, Henning (HERMES - Journal of Language and Communication in Business, 1998)
In this article, the author presents some fundamentals of a modular linguistic approach to argumentation. Argumentation is seen as a matter of interpretation, and since interpretation phenomena depend on linguistic material as well as on context in the broad sense, genuine linguistic theory should be an integrated part of argumentation theory. A linguistic approach to argumentation should adopt instructional semantics as opposed to representational semantics and argumentative (discourse dynamic) seman-tics as opposed to referential semantics. In view of the high complexity of argumentation phenomena, rigour can be obtained only in a strictly modular approach. After a brief overview of the global approach, the author lays down some fundamental metho-dological and theoretical principles for modular studies. He then introduces three modules taking care of Lexical Semantics (the Topos Theory), Polyphony and Argu-mentative Functors. The three mini-theories involved are all inspired by the Theory of Argumentation in Language developed by the French linguists Oswald Ducrot and Jean-Claude Anscombre. Two recommendations for practitioners are formulated as conclusion: “To be efficient, use the right linguistic forms and structures!” and “To choose efficient forms, keep your eye on the purpose!”